Percentage of Mangrove Canopy Cover and Mollusks Abundance in Benoa Bay Mangrove Ecosystem - Tinambunan, Shintani Asri; Pertami, Nyoman Dati; Ernawati, Ni Made (Advances in Tropical Biodiversity and Environmental Sciences; Vol 5 No 3 (2021): ATBES, 2021)
This research was conducted to determine the condition of the mangrove ecosystem based on its canopy cover and to determine the types of mollusks (Bivalves and Gastropods) associated with the Benoa Bay mangrove ecosystem. Hemispherical photography is a method for observing mangrove canopy cover and line transect method for mollusks. The composition of mangrove species found in the research location were five species, namely Rhizophora stylosa, Rhizophora mucronata, Rhizophora apiculata, Bruguiera gymnorrhiza , and Avicennia marina . The percentage of mangrove canopy cover in the Benoa Bay mangrove ecosystem is in a good category (average = 76.59%). There are eight types of mollusks found in the research location. There are two types of bivalves (Polymesoda bengalensis and Gafrarium pectinatum) and six types of gastropods ( Nerita balteata, Nerita picea, Neritina turrita, Pila ampullacea, Cassidula aurisfelis , and Littoraria melanostoma). The relationship between the percentage of mangrove canopy cover and abundance of mollusks in the Benoa Bay mangrove ecosystem is very strong (r) of 0.920. The higher the percentage value of mangrove canopy cover, the higher the mollusks abundance.